2005
DOI: 10.1111/j.1748-1090.2005.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

The future of zoos and aquariums: conservation and caring

Abstract: The success of zoos and aquariums as conservation centres depends on the holistic embrace of conservation, including acting as model citizen, wildlife conservationist, agent for conservation and mentor/trainer. Success also depends on truly reaching our audiences, from policy‐maker to land manager to citizen, to help them care about and care for nature. In pursuing our conservation goal, we must acknowledge our general lack of experience in effectively changing the behaviour of these different audiences, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 75 publications
0
49
0
Order By: Relevance
“…In the first world urban environment, zoos and aquariums provide city dwellers with a similar opportunity to relax with family and friends in a pleasant and safe environment. For both rich and poor, these facilities provide visitors with a chance to connect with nature (Rabb & Saunders, 2005) as they are able to reach across social, cultural and economic barriers and touch people throughout the world.…”
Section: The History Of Zoos and Aquariumsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first world urban environment, zoos and aquariums provide city dwellers with a similar opportunity to relax with family and friends in a pleasant and safe environment. For both rich and poor, these facilities provide visitors with a chance to connect with nature (Rabb & Saunders, 2005) as they are able to reach across social, cultural and economic barriers and touch people throughout the world.…”
Section: The History Of Zoos and Aquariumsmentioning
confidence: 99%
“…In situ conservation efforts include habitat protection and restoration, animal reintroduction and management, supporting local communities and providing expertise to managers in the field. Ex situ conservation efforts include research, captive breeding and animal rehabilitation programmes, and fundraising, in addition to influencing visitors, both directly through education programmes and indirectly as role models for sustainable living (Fraser & Wharton, 2007;Keulartz, 2015;Rabb & Saunders, 2005;Tribe & Booth, 2003).…”
Section: The History Of Zoos and Aquariumsmentioning
confidence: 99%
“…The link between the ethos of zoos and their operations has also been identified as an important area for consideration (Rabb and Saunders, 2005). Townsend (2009) profiled the sustainability practices of 52 BIAZA members but did not compare them with sustainability priorities.…”
Section: Sustainable Food Supply Chains In Zoosmentioning
confidence: 99%
“…To inspire people to take conservation action, zoos and aquariums must not only teach visitors facts about animals but engage them in meaningful experiences that increase care and concern for wildlife (Rabb and Saunders 2005), foster conservation learning and attitudes (Ballantyne et al 2007), and motivate behavior change (Heimlich and Ardoin 2008). A large-scale, multi-institutional assessment published by the Association of Zoos and Aquariums (Falk et al 2007) concluded that, overall, visits to zoos and aquariums have a positive impact on conservation knowledge and attitudes.…”
mentioning
confidence: 99%